Changes of Myogenic Reactive Oxygen Species and Interleukin-6 in Contracting Skeletal Muscle Cells. (14th May 2012) - Pan, Hongying; Xu, Xiaoyang; Hao, Xuanming; Chen, Yajun
Abstract : The aim of this study was to measure changes in myotube reactive oxygen species (ROS) and the production of interleukin (IL)-6 in electrically stimulated mouse C2C12 skeletal muscle cells. After five days of differentiation, myotubes were stimulated using an electrical stimulator set at 45 V at a frequency of 5 Hz, with a pulse width of 20 ms. Acute stimulations were performed for 45, 60, 75, 90, or 120 min in each dish. ROSs were detected in the extracted cells directly using a fluorescent probe. IL-6 mRNA expression in C2C12 myotubes and IL-6 concentration in C2C12 myotube supernatants were determined using real-time PCR and ELISA, respectively. Compared with control cells, ROS generation was significantly increased at 45 min after the onset of stimulation (P < 0.01 ) and continued to increase, reaching a maximum at 120 min. IL-6 mRNA expression and IL-6 concentration in C2C12 cells were significantly increased after 75 min (P < 0.01 ) and 120 min (P < 0.05 ) of electrical stimulation (ES) compared with the control cells. Our data show that a specific ES intensity may modulate ROS accumulation and affect IL-6 gene expression in contracting skeletal muscle cells.